Analysis of the Concept of Child-Friendly Schools that Support Indonesian Insight - Rama Wijaya Abdul Rozak; Siti Nurbayani; Muhamad Jidan Andhika Faturrohman; Armi Alzzaini Alkautzhar; Syifa Fauziah (International Journal of Educational Review, 2026)
This research aims to examine the concept of child-friendly schools in Indonesia resulting from previous research. We also offer a child-friendly school idea with an Indonesian perspective. The study uses a systematic literature review approach. There are several categories of articles that we review, including discussing child-friendly schools, multicultural learning, and Indonesian insights. We searched using the publish or perish application and determined articles published in the last five years. We found that the concept of child-friendly schools has yet to be able to fulfil children's rights, such as security and protection, which can have an impact on children's learning motivation. This is based on KPAI data, which shows that there are still many cases of bullying reported in schools. We propose the concept of a child-friendly school with an Indonesian perspective so that children grow and develop into true entities of Indonesian society, namely polite and tolerant. Child-friendly schools with an Indonesian viewpoint can be used as an alternative solution to create children's potential in a better direction. However, this concept needs to be tested more intensively so that an implementation and evaluation scheme can be drawn.